2011
DOI: 10.1093/cid/cir074
|View full text |Cite
|
Sign up to set email alerts
|

Guillain-Barre Syndrome following Primary Cytomegalovirus Infection: A Prospective Cohort Study

Abstract: This study provides new insights about the epidemiology of CMV-GBS and shows that the risk of developing GBS is similar following primary CMV infection or C. jejuni infection. Our results also suggest a direct or indirect involvement of viral replication in the neuropathological processes of CMV-GBS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
97
4
6

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(116 citation statements)
references
References 37 publications
9
97
4
6
Order By: Relevance
“…However, although the crucial role of Campylobacter jejuni (48) is well established for AMAN, the link between pathogenesis and different viral infections such as CMV (49) or EBV (50) in AIDP patients remain questionable. Herpes viruses-such as cytomegalovirus (CMV), Epstein-Barr virus (EBV) (13,15), and the varicella-zoster virus (VZV-have often been mentioned as possible GBS promoters (58), whereas the herpes simplex virus (HSV-1 and HSV-2) is rarely associated with GBS (59,60). Our results again confirmed that none of the abovementioned viruses were strictly necessary for AIDP progression.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…However, although the crucial role of Campylobacter jejuni (48) is well established for AMAN, the link between pathogenesis and different viral infections such as CMV (49) or EBV (50) in AIDP patients remain questionable. Herpes viruses-such as cytomegalovirus (CMV), Epstein-Barr virus (EBV) (13,15), and the varicella-zoster virus (VZV-have often been mentioned as possible GBS promoters (58), whereas the herpes simplex virus (HSV-1 and HSV-2) is rarely associated with GBS (59,60). Our results again confirmed that none of the abovementioned viruses were strictly necessary for AIDP progression.…”
Section: Discussionsupporting
confidence: 77%
“…Campylobacter jejuni (13,14), Epstein-Barr virus (EBV), cytomegalovirus (CMV) (13,15), and Mycoplasma pneumoniae (13) are among the most common infectious agents that are thought to be able to trigger GBS. Besides, the first strong evidence that Zika virus can cause GBS development was published recently (16).…”
mentioning
confidence: 99%
“…Campylobacter jejuni is the predominant infection triggering GBS worldwide,14 and is associated with severe acute motor axonal neuropathy (AMAN)‐type of GBS with a poor clinical outcome 15. Cytomegalovirus in contrast can cause severe senso‐motoric disorders and a GBS subtype described as acute inflammatory demyelinating polyneuropathy (AIDP) 16. The frequency of these GBS subtypes differs between geographical regions, which is in part explained by the local endemic infections.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, accumulating evidence has indicated that the antecedent infection with C. jejuni enteritis may trigger the generation of AGA (Nyati & Nyati, 2013). Moreover, previous studies have shown that Cytomegalovirus (CMV), a member of the β herpes family may lead to the incidence of GBS and is second only to C. jejuni enteritis (Orlikowski et al., 2011; Taheraghdam et al., 2014). Currently, although there are a number of studies on the AGA and a few studies of anti‐CMV antibodies in GBS, the association between them remains poorly documented (Annunziata, Figura, Galli, Mugnaini, & Lenzi, 2003; McCombe, Wilson, & Prentice, 1992; Taheraghdam et al., 2014).…”
Section: Introductionmentioning
confidence: 99%